Garre’s Osteomyelitis of the Mandible Caused by Infected Tooth - Hayati Murat Akgül; Fatma Çağlayan; Sevcihan Günen Yılmaz; Gözde Derindağ (Case Reports in Dentistry)
Aim. Garre’s osteomyelitis is a local thickening of the periosteum caused by a slight irritation or infection. We aimed to present the extraoral, intraoral, and radiographic findings and postoperative pursuits of two patients diagnosed with Garre’s osteomyelitis. In this case report, although clinical findings indicate infection source, these clinical findings are strongly supported by cone-beam computed tomography images. In addition, it can be seen that when we have followed the case I, we have chosen the right path in treatment. Case Reports. Two patients presented to our clinic due to severe swelling and facial asymmetry in the right and left mandibular region. As a result of the clinical and radiological examinations, the patients were diagnosed with Garre’s osteomyelitis. Infected teeth that were responsible for the formation of Garre’s osteomyelitis were extracted under antibiotic treatment in both cases. A complete improvement in postoperative control was observed in case I. On the other hand, the other case could not be followed up postoperatively. Conclusion. In Garre’s osteomyelitis, new bone formation can occur in many pathological conditions. Therefore, it should be distinguished from other pathologies that cause new bone formation, such as Ewing’s sarcoma, Caffey disease, and fibrous dysplasia.